PELECEHAN SEKSUAL, KEWAJIBAN MELAPOR DAN RESPONS ORDINARIS: TELAAH KRITIS “VOS ESTIS LUX MUNDI” DAN “VADEMECUM” - Rikardus Jehaut (Jurnal Ledalero, 2021)
This article aims to examine the question of sexual abuse of minors and vulnerable adults by clerics and members of the Institute for Consecrated Life and the Society for Apostolic Life in the light  of  motu proprioVos Estis Lux Mundi and Vademecum.  It starts with a brief description of sexual abuse, the  mandatory report  and  then  the  response of the Ordinary.  It shows that sexual abuse is a grave delict, and clerics or religious who have knowledge of information  are obliged to report it to the Ordinary while  maintaining the seal of confession,  and the Ordinary has the grave obligation  to take any reports  seriously, promptly and decisively, taking into consideration  that the procedural  norms  should be carefully observed. By using the analytical and critical method, the author argues that it is of the highest importance for the Ordinary to establish a system for receiving reports as well as preparing competent  personnel in order to handle the  case in a  thorough  and  expeditious manner. Key words: sexual abuse, minors, vulnerable adults, mandatory report, Ordinary